2020 IEEE 8th Electronics System-Integration Technology Conference (ESTC) 2020
DOI: 10.1109/estc48849.2020.9229696
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cu-Sn-In system for low temperature, wafer level solid liquid inter-diffusion bonding

Abstract: The Solid Liquid Interdiffusion (SLID) bonds carried out for this work take advantage of the Cu-In-Sn ternary system to achieve low temperature wafer-level bonds.The experiments were carried out across a range of temperatures and the results cover optimized wafer-level bonding process, the formation of the bond microstructure, mechanical performance, as well as the effects of thermal aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The objective is to study the possibilities of low-temperature wafer-level SLID bonding down to 170C utilizing ternary Cu-In-Sn metallurgy at bonding temperatures, that are below currently demonstrated solutions [33][34][35]. Additionally, the effect of bonding temperature on the bond quality, microstructure defect formation, and mechanical reliability will be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to study the possibilities of low-temperature wafer-level SLID bonding down to 170C utilizing ternary Cu-In-Sn metallurgy at bonding temperatures, that are below currently demonstrated solutions [33][34][35]. Additionally, the effect of bonding temperature on the bond quality, microstructure defect formation, and mechanical reliability will be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature, the stable phases in Cu-In binary system are Cu, , and In. Based on the previous experimental results and the Cu-In binary phase diagram, various IMCs (Cu7In3 (δ), Cu2In (η), Cu11In9, CuIn2, Cu16In9, and CuIn ) can appear during bonding [2], [3], [10]- [13], [16], [17], and phase transformation can occur during aging. Voids with different sizes appear after aging due to the volume shrinkage between different phases [15].…”
Section: Introductionmentioning
confidence: 89%
“…In the higher bonding temperature, the Cu-Sn-In joints comprise a single Cu3Sn and Cu3(Sn,In) phase, respectively. [1], [3]. It has been demonstrated that indium can stabilize the Cu6Sn5 phase and hinder the Cu3Sn phase formation and correspondingly void formation [1].…”
Section: A Microstructural Evolutionmentioning
confidence: 99%
See 2 more Smart Citations